2014
DOI: 10.1377/hlthaff.2013.0939
|View full text |Cite
|
Sign up to set email alerts
|

Restrictions On Pharmaceutical Detailing Reduced Off-Label Prescribing Of Antidepressants And Antipsychotics In Children

Abstract: The treatment of pediatric depression is controversial because it includes substantial prescribing of drugs for uses that have not been approved by the Food and Drug Administration ("off label") and are not evidence based. Some academic medical centers (AMCs) restrict "detailing" by pharmaceutical sales representatives, or the promoting of drugs directly to physicians via sales calls, to reduce the effect of such marketing on physician prescribing. With data from thirty-one geographically diverse AMCs and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Mounting evidence suggests that medical school conflict of interest policies have a significant impact on prescribing (King et al, 2013; Epstein et al, 2013; Larkin et al, 2014). This work has also found that more restrictive policies have a stronger effect on prescribing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence suggests that medical school conflict of interest policies have a significant impact on prescribing (King et al, 2013; Epstein et al, 2013; Larkin et al, 2014). This work has also found that more restrictive policies have a stronger effect on prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent empirical research has found that medical school policies limiting or prohibiting detailing lead to lower rates of new drug uptake (King et al, 2013), higher rates of generic prescribing (Epstein et al, 2013), and reduced off-label prescribing (Larkin et al, 2014). While this work has significantly advanced our understanding about the impact of medical schools’ conflict of interest policies, three gaps remain in the existing literature.…”
mentioning
confidence: 99%
“…A number of strategies, including prior authorization and step therapy requirements, 3944 tiered formularies, 45,46 monitoring and feedback (e.g., computerized alerts, reminders, audit and feedback), 47 academic detailing, 48,49 and policies restricting detailing efforts by pharmaceutical manufacturers 50 have proven effective at influencing physician prescribing behavior in general. Payers and health plans could consider applying these approaches to antipsychotic prescribing to young children in an effort to highlight for prescribers the risk-benefit tradeoffs associated with antipsychotic use in children.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from teaching about industry practices of marketing and promotion, restrictive COI policies at the medical school level have been suggested to increase students' awareness of the consequences of inappropriate marketing practices in the learning environment (22). Some studies indicate that COI policies at medical schools have a significant impact on prescribing practices and inoculate physicians against persuasive aspects of pharmaceutical promotion (23)(24)(25). These studies also show that more restrictive policies were associated with higher compliance of physicians' prescriptions with current guidelines (23)(24)(25).…”
Section: The Role Of Conflict Of Interest Policies At Medical Schoolsmentioning
confidence: 99%
“…Some studies indicate that COI policies at medical schools have a significant impact on prescribing practices and inoculate physicians against persuasive aspects of pharmaceutical promotion (23)(24)(25). These studies also show that more restrictive policies were associated with higher compliance of physicians' prescriptions with current guidelines (23)(24)(25). It has not been clarified which components of a COI policy might have a particularly important impact on physicians' behaviour and attitudes.…”
Section: The Role Of Conflict Of Interest Policies At Medical Schoolsmentioning
confidence: 99%